Thermal Analysis of Photo Voltaic System for Impact Assessment on Seasons for Power Generation - , B.A Anand; , Tejas K.S; , H.K. Venkat Reddy (Archives of Current Research International, 2025)
In photovoltaic systems the performance is basically influenced by various factors, including temperature, irradiance, and seasonal changes. In this study the thermal behavior of PV systems and assesses the impact of seasonal variations on their power generation efficiency at the designated power plant has been studied. By analyzing temperature fluctuations over different seasons, we aim to better understand the relationship between ambient temperature, surface temperature of PV panels, and their electrical output. Seasonal changes, particularly the higher temperatures in summer and lower temperatures in winter, significantly influence the efficiency of photovoltaic systems. The results show that while PV systems generate more power during high-irradiance months, their efficiency can be compromised by elevated temperatures. The findings provide valuable insights for improving PV system efficiency in varying climatic conditions and guide the development of more sustainable and reliable energy generation solutions.